The Social Consequences of the Presence of Muslims in Andalusia - Mohammad Ali Chalungar; Parvin Asqari (تاریخ اسلام)
In the very last years of the first century After Hijrah and simultaneous with the first decades of the eighth century A.D, it was opened the gates of Andalusia by Muslim conquerors and in this land, the government of Muslims changed into a place for perfection of Islamic civilization around eight centuries. Providing the necessary conditions for the peaceful coexistence of various nations and the intellectual indulgence and toleration, the Islamic civilization had changed into a place for the Iranian, Indian and Roman civilizations and at this time, it had entered into a new land with particular properties. The attractions of Islamic culture and civilization led to the tendency of Christians of Andalusia towards the Muslims’ traditions while preserving their own rituals.  Muslims provided a peaceful atmosphere with appropriate conditions in favor of the interaction in the diverse religious, cultural and social grounds. This research tries to investigate the social consequences of the presence of Muslims in Andalusia in the issues such as the family system, clothing, nourishment and the way of serving, health and the administration of religious traditions.